OVERVIEW OF THE FISCAL POLICY EXISTING IN THE COUNTRY AND THE WAYS FOR ACHIEVING EXCELLENCE - Tamar Gamsakhurdia (European Scientific Journal, ESJ, 2014)
Global financial crisis had impact on macroeconomic situation of Georgia by decreasing export and changing other indicators related to crisis. Consequently, in response to the challenges of the financial crisis, scientific research of fiscal policy will be rather important in order to carry out such measures which will ensure fitting fiscal instruments with other fields of the state policy what implies, on the one hand, using the tax system for establishing new work places in separate sectors and regions as well as overcoming poverty, making decentralization reforms and, on the other hand, searching the ways for hardening the fiscal policy from the point of view of monitoring, planning, spending and auditing public expenses. In the process of the research are used general scientific methods (systemic, structural, functional) and private methods (graphic and those of conformity). Official statistical data existing in the country as well as the data and evaluations officially published by international organizations are also used.